Enhancing broadband development and internet usages for improving networks and services in APEC member economies: Bridging the digital divide - Markus Fredebeul-Krein; Markus Steingröver (International Telecommunications Society (ITS), 2012)
The competitiveness of a country and entire regions today is strongly connected to its broadband adaptation. Broadband is not only playing a critical success role in the economy, it connects consumers, businesses, governments and facilitates social interaction. Many studies have been carried out over the last decade in the APEC region highlighting the status and the different developments of broadband in each economy. The e-APEC strategy and its goal to enable the people in urban, provincial and rural communities in every economy to have individual or community-based access to information and services via the internet by 2010 have been largely achieved. Embedded are the key principles for broadband development to maximize access and usage, to facilitate continued competition and liberalization, to foster enabling regulatory frameworks and to build confidence in the use of broadband networks and services. Future prospects and the recommendations of APEC ministers are to set an ambitious goal of access to next generation high-speed broadband by 2020 to expand and improve ICT infrastructure for knowledge-based economies in the APEC region. In a recent meeting in Okinawa the commitments towards achieving the goal of universal access to broadband in the APEC region by 2015 were reaffirmed...
Keywords: 330